2021
DOI: 10.3390/metabo11100648
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Lipidomic Patterns in Patients with Symptomatic Coronary Microvascular Dysfunction

Abstract: Coronary microvascular dysfunction (MVD) is a syndrome of abnormal regulation of vascular tone, particularly during increased metabolic demand. While there are several risk factors for MVD, some of which are similar to those for coronary artery disease (CAD), the cause of MVD is not understood. We hypothesized that MVD in symptomatic non-elderly subjects would be characterized by specific lipidomic profiles. Subjects (n = 20) aged 35–60 years and referred for computed tomography coronary angiography (CTA) for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
(40 reference statements)
0
3
0
Order By: Relevance
“… 46 , 47 Lower blood concentrations of long-chain fatty acid acylglycerols have been identified as a potential contributor to ANOCA, possibly through metabolic insufficiency for fatty acid oxidation and reduced metabolic efficiency. 48 Abnormal ratios of certain eicosanoid metabolites of arachidonic acid have also been associated with ANOCA, consistent with their role in regulating vascular tone. 49 Epicardial adipose tissue has been associated with ANOCA 50 and is also known to be a source of specific lipidomic features that are thought to act in a paracrine fashion to promote CAD and possibly abnormal vasoactive tone.…”
Section: Incorporating Precision Medicine Into Anoca Diagnosis and Tr...mentioning
confidence: 85%
“… 46 , 47 Lower blood concentrations of long-chain fatty acid acylglycerols have been identified as a potential contributor to ANOCA, possibly through metabolic insufficiency for fatty acid oxidation and reduced metabolic efficiency. 48 Abnormal ratios of certain eicosanoid metabolites of arachidonic acid have also been associated with ANOCA, consistent with their role in regulating vascular tone. 49 Epicardial adipose tissue has been associated with ANOCA 50 and is also known to be a source of specific lipidomic features that are thought to act in a paracrine fashion to promote CAD and possibly abnormal vasoactive tone.…”
Section: Incorporating Precision Medicine Into Anoca Diagnosis and Tr...mentioning
confidence: 85%
“…We found that the application of lipidomics in CAD or atherosclerosis can be broadly divided into 2 categories by tracing the relevant primary literature. One of the 2 categories is to explore the lipid profiles of different disease subtypes, such as the characteristic lipid species of symptomatic coronary microangiopathy and acute myocardial infarction, [37][38][39] and the lipid profiles of plaques at different stages of atherosclerosis development. [40] The other is to explore the mechanisms of therapeutic effects based on lipidomic testing, such as proprotein convertase subtilisin/kexin type 9 inhibitors, [41,42] lifestyle interventions such as diet structure adjustment, limitation of smoking and alcohol consumption, and the intervention of effective active ingredients in Chinese herbs.…”
Section: Discussionmentioning
confidence: 99%
“…From time‐intensity curves, a microvascular blood volume (A) value near 150 IU at rest and stress, and a microvascular flux rate (β) near 0.8 and 2.5 s −1 during rest and stress respectively were considered normal. 12 Microvascular blood flow was quantified by the product of microvascular blood volume and β. Flow reserve (β reserve) was calculated as the ratio of values obtained during regadenoson to those at rest.…”
Section: Case Reportmentioning
confidence: 99%